Implementasi Program Gotong Royong Di Desa Lompad Kecamatan Ranoyapo Kabupaten Minahasa Selatan - Eunike Piay; Masje Pangkey; Novie Palar (JURNAL ADMINISTRASI PUBLIK, 2023)
This study aims to find out how the implementation of the Gotong Royong Program in Lompad Village, Ranoyapo District, South Minahasa Regency. By using qualitative research methods. Informants in this study were Old Law, Village Secretary, Head of BPD, Head of Environment, Leaders, and the Community. The focus of this research is seen from the 3 indicators that support the running of the program which include organizing, interpretation, and application or application. . Organizing requires a clear organizational structure in carrying out the program so that implementing staff can be formed from competent quality human resources and organizing the mutual cooperation program in Lompad Village, Ranoyapo District, South Minahasa Regency,